Severe OCD Exacerbation in a Patient with Autism Spectrum Disorder: A Case Report - Gray, Jasmine; Bazargan-Hejazi, Shahrzad; Ebrahim, Gul; Cho, Daniel (Archives of Clinical and Medical Case Reports, 2021)
Autism Spectrum disorder (ASD) is a neurodevelopmental disorder characterized by impairments in social communication and social interaction, repetitive and stereotyped behaviors, and /or sensory aberrations. On the other hand, obsessive-compulsive disorder (OCD) is characterized by the presence of obsessions and/or compulsions. In consideration of these distinct pathologies, research suggests that anxiety disorders and OCD are highly prevalent in individuals with ASD. This case report will discuss an adolescent patient with ASD and OCD who experiences an exacerbation, most notably, in his symptoms of OCD. We outline the hospital course of a 13 year-old male who ultimately requires nasogastric (NG) tube feeding resulting from an acute worsening in symptoms and refusal of oral intake during the COVID-19 pandemic. The patient demonstrated significant improvement in symptoms following the administration of high-dose selective serotonin reuptake inhibitor (SSRI) and low-dose antipsychotic therapy.